Formation evaluation and well-test analysis for complex interpretation of reservoir permeability distribution; IOP Conference Series: Earth and Environmental Science; Vol. 21: XVIII International Scientific Symposium in Honour of Academician M. A. Usov: Problems of Geology and Subsurface Development 7–11 April 2014, Tomsk, Russia - Korovin M. O. Mikhail Olegovich (Exploration Geophysics, Mineral Exploration, 2014)
Title screen